SME credit constraints and macroeconomic effects - Petra Gerlach-Kristen; Brian O'Connell; Conor O'Toole (The Economic and Social Research Institute (ESRI), 2013)
This research attempts to answer two particular questions: a) what factors drive SME credit constraints in the Irish economy and b) what is the impact of such constraints on the macro-economy, in particular on employment and investment. We find that constraints decrease with firm size while there is variation by sector. Our results indicate that firms applying to foreign-owned banks are more likely to be constrained. We also identify a direct effect of debt overhang on access to credit. Linking constraints to the macro-economy, we find a negative and significant effect of SME credit constraints on employment, while no effect is evident on firm investment.
Keywords: 330; Financial Crisis; Credit Constraints; Investment; Employment; SMEs